2015
DOI: 10.1093/neuonc/nov081
|View full text |Cite
|
Sign up to set email alerts
|

Decreased affinity for efflux transporters increases brain penetrance and molecular targeting of a PI3K/mTOR inhibitor in a mouse model of glioblastoma

Abstract: GDC-0980 is subject to active efflux by P-gp and BCRP at the BBB, while brain penetrance of GNE-317 is independent of efflux, which translates into enhanced inhibition of PI3K/mTOR signaling. These data show that BBB efflux by P-gp and BCRP is therefore an important determinant in both brain penetrance and molecular targeting efficacy in the treatment of invasive glioma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…2325 NPs were synthesized with encapsulation of IR780, a near-infrared fluorescent dye that allows for non-invasive detection using an IVIS imaging system. We found that mHph2-III-62% NPs had limited ability to penetrate the BBB in tumors but that further conjugation with chlorotoxin (CTX) enhanced the delivery by 1.9 fold (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…2325 NPs were synthesized with encapsulation of IR780, a near-infrared fluorescent dye that allows for non-invasive detection using an IVIS imaging system. We found that mHph2-III-62% NPs had limited ability to penetrate the BBB in tumors but that further conjugation with chlorotoxin (CTX) enhanced the delivery by 1.9 fold (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of many drugs is significantly lower at the infiltrating GBM rim as compared to the necrotic tumor core(28). This impaired drug delivery to infiltrating glioma may be associated with diminished efficacy of these drugs in orthotopic glioma models (32, 4143). TAL mirrors these experiences by demonstrating a lack of orthotopic efficacy despite activity in heterotopic models.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are now reaching clinical trials, an exciting landmark in targeted CNS therapeutics. Other groups are investigating inhibition of efflux mechanisms to maintain drug levels in the NVU (95,96). Successful modulation of these endogenous transport systems will prove critical to drug delivery in the NVU.…”
Section: Future Directionsmentioning
confidence: 99%